Successful total hip arthroplasty in patients with anca-associated systemic vasculitis - T. V. Beketova; E. A. Naryshkin; E. V. Arsenyev; M. A. Makarov (Научно-практическая ревматология, 2019)
The retrospective study enrolled 8 patients with ANCA-associated  systemic vasculitis (AASV) and hip joint (HJ) injury with indications for total hip arthroplasty (HA); a total of 11 HJs were operated on. The patients’ median age at the time of the first HA was 54 [31; 76] years. The median duration of follow-up after HA was 3 [0.5 to 12.5] years. Wegener’s granulomatosis was diagnosed in 5 patients; microscopic polyangiitis in 2 patients, and eosinophilic granulomatosis polyangiitis (or Churg-Strauss  syndrome) in one case. At the onset of AASV, the median Birmingham Vasculitis Activity Score (BVAS) was 12 [6; 26]; four patients had a 5-year mortality rate of 21% (Five-Factor Score (FFS)  = 1). AASV remission was induced by anti-B cell therapy with rituximab (RTM) in 6 patients. A total of 10 total HAs were performed for aseptic necrosis of the femoral head and another HA was carried out for a femoral neck fracture. At the time of HA, complete remission (BVAS = 0) was observed in 7 cases of AASV; incomplete remission (BVAS = 3) was seen in one patient. All endoprosthesis  components  were stable; there were no signs of osteolysis. In all cases, HA was successful in increasing HJ functional activity and in reducing pain (the Harris hip score averaged 54 before HA and 87 at 6 months after surgery). None of the patients had AASV recurrence  or developed postoperative complications  (except for the need for blood transfusion).The authors’ own experience suggests that total HA is a potentially highly effective and relatively safe treatment in patients with AASV, including those with severe AASV and unfavorable prognostic factors. To reduce the risk of postoperative complications  (primarily thromboembolism, infections, and RTM-induced late-onset  neutropenia), total HA should be performed in the period of AASV remission under the control of comorbid conditions  and in the close cooperation  of rheumatologists  and orthopedic  surgeons. The following recommendations for the management of patients with rheumatic diseases should include patients with AASV for elective total HA.